2022
DOI: 10.1097/mca.0000000000001198
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation in coronary artery disease-clinical implications of novel HDL-cholesterol–related inflammatory parameters as predictors

Abstract: Coronary artery disease (CAD) is the leading cause of death worldwide. Inflammation and atherosclerotic plaques are the primary pathological mechanisms of CAD. Upon stimulation by deposited lipids and damaged endothelium, innate and adaptive immune cells are activated and recruited to initiate plaque development. Therefore, inflammatory cells and mediators are used to identify inflammatory risk in CAD patients. HDL-cholesterol (HDL-C) is demonstrated to have anti-inflammatory roles in atherosclerosis by interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 118 publications
1
3
0
Order By: Relevance
“…The results of the current study, Table (4), indicated that there was a decrease in the level of high-density lipoprotein in the first and second groups compared with the third group, but it was not statistically significant. These results are consistent with the study [39] and the study of [40], The low level of high-density lipoprotein may be due to several reasons, either due to diabetes [41] or cigarette smoking [42] or due to inflammatory factors [43]. Also, women who use oral contraceptives that contain progestin [44] have low HDL cholesterol.…”
Section: Discussionsupporting
confidence: 88%
“…The results of the current study, Table (4), indicated that there was a decrease in the level of high-density lipoprotein in the first and second groups compared with the third group, but it was not statistically significant. These results are consistent with the study [39] and the study of [40], The low level of high-density lipoprotein may be due to several reasons, either due to diabetes [41] or cigarette smoking [42] or due to inflammatory factors [43]. Also, women who use oral contraceptives that contain progestin [44] have low HDL cholesterol.…”
Section: Discussionsupporting
confidence: 88%
“…Several reports have shown the anti-inflammatory effects of HDL-C through its interaction with immune cells. 35 HDL-C suppresses the expression of adhesion molecules on monocytes and inhibits their recruitment into the vessel wall. 36,37 HDL-C also promotes the differentiation of monocytes into M2 macrophages and contributes to the expression of anti-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Apo(a) undergoes oxidation and partial proteolysis by metalloproteinases, which contribute to the development of an atheromatous plaque. Recent review publications, such as those by Mehta (2022) [402], Lu (2022) [403], Di Giovanni (2023) [404], Ronda (2023) [405], Bellot (2023) [406], Guo (2023) [407], Močnik (2023) [408], Kim (2023) [409], and Poznyak (2023) [410], have detailed the pathogenetic role of impaired Lp metabolism in atherogenesis. It has been shown that all Lp-containing apoB-100 is associated with atherosclerosis.…”
Section: Role Of Lipoprotein Metabolism Dysfunction In the Pathogenes...mentioning
confidence: 99%